ISOLASI DAN IDENTIFIKASI SENYAWA TERPENOID YANG AKTIF ANTIBAKTERI PADA HERBA MENIRAN (Phyllanthus niruri Linn) - Gunawan, I W. G.; Gede Bawa, I G. A.; Sutrisnayanti, N. L. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008)
Isolation and identification of terpenoid, antibacterial compounds meniran herb (Phyllanthus niruri Linn) by Gas Chromatography – Mass Spectroscophy were carried out. Two kinds of extraction, i.e. maseration using methanol and the sochlet using n-hexane were employed. The extract obtained were contains terpenoids basedon fitochemical test of Liberman-Burchard n-hexane extract was tested for antimicrobial activity against Escherichia coli ATCC® 25292 and Staphylococcus aureus ATCC® 25293. In this study we obtained that n-hexane extract by sochlet extraction showed greater activity compared to the extract by maseration with methanol, as indiated by disc diameter of inhibition zone. Diametric inhibition zone for these two extract are 1 mm for Escherichia coli and 0,5 mm for Staphylococcus aureus, for methanol extract, and where are 10 mm for Escherichia coli and 12 mm for Staphylococcus aureus for n-hexane extract. The n-hexane extract was then purified using column chromatography. The pure extract was analyzed using Gas Chromatography - Mass Spectroscophy. Gas Chromatography - Mass Spectroscophy data indicated that the extract contains two compounds, i.e. phytadiene [ M+ ] 278 and 1,2 seco – cladiellan m/z 335 [ M+ - H ].
Keywords: Phyllanthus niruri Linn, terpenoid, active againts bacteria